Swallow Nest Tax Control in Cirebon Regency - Heru Kuswandi; Rita Myrna; Nina Karlina (Universitas Padjadjaran, 2020)
This research investigates swallow nest tax controlling in Cirebon Regency. The swallow nest tax is tax on the activity of taking or exploiting swallow nest. Formulation of the problem in this study is based on the report issued by THE BPPD Cirebon Regency, which showed that there was tax disobedience or avoidance performed by the swallow nest taxpayers. There was also still lack of corrective action done by the government in deciding tax penalty for the tax breakers. It is assumed to happen due to the less optimized controlling process. Therefore, this research aimed at seeing how the controlling process of swallow nest tax in Cirebon Regency was conducted. The data collecting technique of the qualitative method was applied in this research by using the literature research, field research, and interviewing five informants. They were the Head of Control Sub-Department of THE BPPD of Cirebon Regency, the Head of Regional Tax 1 Department of THE BPPD of Cirebon Regency, the Head of Technical Implementation Unit (UPT) of THE BPPD of Cirebon Regency, the taxpayer, and the guard of swallow nest building. The research showed that the swallow nest tax collecting process in Cirebon Regency was not optimal at that time. It was because the performance had not met the determined target, the controlling process done had not been completely conducted based on the standard determined in the Regent’s Regulation (Perbup) No. 14 of 2012, and the commitment in deciding needs of corrective action was not strong enough.